Radioterapie nádorů s plicní lokalizací u idiopatické plicní fibrózy - Kolek, V; Vašáková, M; Šterclová, M; Cwiertka, K; Vrána, D; Kudláček, A; Skřičková, J; Pešek, M; Petera, J (Klinicka onkologie, 2017)
BACKGROUND: This article is a joint statement of the Czech Pneumological and Physiological Society and the Czech Society for Radiation Oncology, Biology and Physics, and reviews current opinions on radiotherapy in patients with idiopathic pulmonary fibrosis (IPF). In general, radiotherapy of lung tumours is associated with risk of radiation pneumonitis (RP); moreover, IPF may be complicated by acute exacerbations (AE-IPF). Both complications may immediately threaten patients lives. MATERIAL AND METHODS: Assessment of individual radiotherapy modalities has shown that conventional radiotherapy is not appropriate, especially in large tumours. Up to 30% of patients are at risk of developing AE-IPF. As a result, as many as 83% of patients die within 3 months of initiation of lung cancer treatment. Fatal RP is most commonly observed within 2 months of radiotherapy. In IPF accompanied by early-stage non-small cell lung cancer (NSCLC), stereotactic body radiation therapy (SBRT) may be considered. NSCLC should be treated with chemotherapy. Several cases report severe exacerbations of subclinical IPF after SBRT even with minimal signs of previous interstitial involvement. Grade 2 RP has been reported in up to 50% of cases with any level of interstitial change detected by lung CT prior to radiotherapy. In palliative radiotherapy, external radiation may be considered as an exception if the main bronchi are involved. Similarly, brachytherapy may be indicated for certain cases of bronchial stenosis. RESULTS: The presence of any level of interstitial change suggests a risk for fatal RP and AE-IPF. This is also supported by the fact that, at the present time, there are no dose limitations for radiation therapy of lung cancer in IPF, irrespective of whether conventional fractionated radiotherapy or SBRT is used. Moreover, there are no reliable predictive factors for lung involvement. In some studies, RP was more frequently associated with high CRP and LDH levels, PS 2 and interstitial changes of 10% or more. Treatment depends on the severity of the involvement. In more severe forms, corticosteroids, antibiotics and oxygen therapy should be administered. Ventilation support is often needed. CONCLUSION: Radiotherapy for patients with IPF and lung cancer or other chest tumours requires an individual approach depending on the local findings, the patients lung function and general condition, and the prognosis of the primary disease. Decision-making should take into consideration potential benefits and risks, and be carried out by a multidisciplinary team comprising a pulmonologist and clinical and radiation oncologists. Treatment should always be thoroughly discussed with the patient signing an informed consent form.Key words: idiopathic pulmonary fibrosis - chest radiotherapy - indications - radiation pneumonitis - acute exacerbation of idiopathic pulmonary fibrosis - treatment This work was supported by grant AZV 16-32-318 A. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 4. 5. 2017Accepted: 18. 5. 2017.
Keywords: Carcinoma, Non-Small-Cell Lung; akutní nemoc; idiopatická plicní fibróza; Acute Disease; lidé; radioterapie; Disease Progression; Radiation Pneumonitis; radiační pneumonitida; Radiotherapy; Idiopathic Pulmonary Fibrosis; radiochirurgie; Humans; Radiosurgery; nemalobuněčný karcinom plic; progrese nemoci; Lung Neoplasms; nádory plic